The Influence of Digital Money, Financial Inclusion, and Investment on Economic Growth in Indonesia - Amsilah, Amsilah; Kenedi, Kenedi; Agustini, Anti Wulan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The rapid growth of digital finance has reshaped economic activities in emerging markets, including Indonesia. As financial technology evolves, understanding its influence on economic development becomes increasingly important. This study aims to examine the impact of digital money, financial inclusion, and investment on economic growth in Indonesia from 2009 to 2023. A quantitative approach was employed using the Autoregressive Distributed Lag (ARDL) model to analyze annual time series data. The results reveal that in the long run, all three variables digital money, financial inclusion, and investment significantly and positively influence economic growth. Investment had the largest impact, followed by financial inclusion and digital money. In the short run, digital money and investment remain significant, while financial inclusion shows a lagged negative effect. The error correction term is significant and negative, confirming a stable long-run relationship. The findings underscore the importance of promoting investment and strengthening digital and financial infrastructure to enhance both immediate and sustained economic performance in Indonesia’s digital economy.